The shock Hugoniot of hydroxy-terminated polybutadiene - Meziere, Y.; Akhavan, Jacqueline; Stevens, G. S.; Millett, Jeremy C. F.; Bourne, Neil K. (American Institute of Physics (AIP), 2004)
The response of polymers to shock loading is becoming of increasing importance, both as binder systems in plastic-bonded explosives (PBXs) and as structural materials in their own right. In this paper, we report on the shock Hugoniot of hydroxy-terminated polybutadiene (HTPB), which is commonly used as a binder system in PBXs, but whose shock response has yet to be presented in the open literature. Results indicate that the shock velocity --- particle velocity relationship is linear, similar to some but not all polymer-based materials.